2007
DOI: 10.1111/j.1530-0277.2007.00404.x
|View full text |Cite
|
Sign up to set email alerts
|

Up‐Regulation of Myocardial L‐Type Ca2+ Channel in Chronic Alcoholic Subjects Without Cardiomyopathy

Abstract: Chronic alcoholism causes an up-regulation of myocardial L-type Ca(2+) channel receptors, which decreases when cardiomyopathy is present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…A similar situation was found in aorta, where endothelial NOS, CuZnSOD, MnSOD, and GPx, but not catalase (CAT) levels and activities were increased (Ulker et al 2003;Racasan et al 2005). In humans, superoxide dismutase activity was related to the presence of cardiac enlargement and the degree of cardiac histological damage (Fatjó et al 2005).…”
Section: Introductionmentioning
confidence: 54%
“…A similar situation was found in aorta, where endothelial NOS, CuZnSOD, MnSOD, and GPx, but not catalase (CAT) levels and activities were increased (Ulker et al 2003;Racasan et al 2005). In humans, superoxide dismutase activity was related to the presence of cardiac enlargement and the degree of cardiac histological damage (Fatjó et al 2005).…”
Section: Introductionmentioning
confidence: 54%
“…Excitation–contraction coupling could be disturbed at the level of the sarcolemma, at the sarcoplasmic reticulum, at the mitochondria, and between calcium and the regulatory proteins. L‐type Ca 2+ channels, involved in excitation–contraction coupling, are disturbed in animal models of persistent ethanol consumption . A report from Aistrup expands our understanding of the changes in cellular excitation–contraction coupling in cardiac myocytes during the transition period where acute ethanol exposure becomes chronic.…”
Section: Pathophysiological Mechanismsmentioning
confidence: 91%
“…L-type Ca 2þ channels, involved in excitation-contraction coupling, are disturbed in animal models of persistent ethanol consumption. 61 A report from Aistrup 62 expands our understanding of the changes in cellular excitation-contraction coupling in cardiac myocytes during the transition period where acute ethanol exposure becomes chronic. After the onset of chronic ethanol consumption, the welldocumented negative inotropic effect of acute ethanol exposure is temporarily counteracted by adaptive mechanisms, leading to the expression of a temporary positive inotropic effect.…”
Section: Calcium Homeostasismentioning
confidence: 99%
“…Furthermore, long‐term alcohol exposure in rats resulted in increased activity of protein kinase C, which may be associated with changes in the regulation of cardiac LTCC . Moreover, in human samples, researchers found that chronic alcoholism results in upregulation of myocardial LTCC . In this study, we identified LTCC as the major transporter required for iron entry into cardiomyocytes in the alcohol‐induced myocardial iron‐overload model.…”
Section: Discussionmentioning
confidence: 73%